2019
DOI: 10.1016/j.ecss.2018.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Cross and long-shore variations in reef fish assemblage structure and implications for biodiversity management

Abstract: Highlights  Differences in fish assemblages were found across a shallow reefline gradient.  Species richness and abundance increased from inshore to offshore reefs.  Patterns in composition between reeflines were consistent among locations.  Between reefline differences were greater than differences between locations.  These differences have implications for fisheries and marine biodiversity conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
1
4
0
Order By: Relevance
“…The authors investigated fish assemblage compositions along an inshore-to-offshore gradient (3-23 m depth) and in two marine reserves in Western Australia, 70 km apart. Their findings revealed that the depth and distance from the shore had a substantial effect on the richness and quantity of fish species in the two studied locations [61]. Similar results were reported by McLean et al (2016) in the Pilbara bioregion in north-western Australia [62].…”
Section: Pioneering Countries With a Hard Sustainability Approach In ...supporting
confidence: 65%
See 2 more Smart Citations
“…The authors investigated fish assemblage compositions along an inshore-to-offshore gradient (3-23 m depth) and in two marine reserves in Western Australia, 70 km apart. Their findings revealed that the depth and distance from the shore had a substantial effect on the richness and quantity of fish species in the two studied locations [61]. Similar results were reported by McLean et al (2016) in the Pilbara bioregion in north-western Australia [62].…”
Section: Pioneering Countries With a Hard Sustainability Approach In ...supporting
confidence: 65%
“…According to Bach et al (2019), there are still insufficient benthic habitat maps in Australia, making it challenging to establish reserved areas for biodiversity in MSP with a habitat-based management approach. The authors investigated fish assemblage compositions along an inshore-to-offshore gradient (3-23 m depth) and in two marine reserves in Western Australia, 70 km apart.…”
Section: Pioneering Countries With a Hard Sustainability Approach In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…), or were oblique to the camera with neither the head nor tail visible, we allocated that fish a mean length which was based on that specific species from within the same habitat (similar to Ref. 55 ). Classification of feeding guilds for fish were sourced from FishBase based on the ecology and/or diet descriptions 54 (See Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…sponges) also compete with corals and point to the need to consider the effects of other benthic foragers on coral settlement and survival (Elliott et al 2016;Madduppa et al 2017) Foraging impacts vary with species traits, therefore impacts delivered collectively by a fish assemblage also vary according to the distribution and composition of these traits (Cheal et al 2010). The species and trait composition of fish assemblages vary widely across space in coral reefs, depending on structural complexity of the habitat and environmental gradients (Cheal et al 2012;Darling et al 2017;Richardson et al 2017;Bach et al 2019). The trait variation within an assemblage results in highly differentiated strategies between species (trait complementarity) or similar overlapping strategies (trait redundancy).…”
Section: Introductionmentioning
confidence: 99%